Topical Tacrolimus and Periodontal Therapy in the Management of a Case of Oral Chronic GVHD Characterized by Specific Gingival Localization. (11th December 2013) - Conrotto, Davide; Broccoletti, Roberto; Carcieri, Paola; Giaccone, Luisa; Arduino, Paolo G.
Abstract : Background . Chronic graft versus host disease (cGVHD) is a complication following bone marrow transplantation. The oral lesions are difficult to control with a systemic pharmacological therapy. Case Description . A 63-year-old female patient, who underwent an allogeniec transplantation for acute myeloid leukemia, developed a chronic oral and cutaneous GVHD. The patient was treated with topical tacrolimus 0.1%, twice daily for two months, and underwent a protocol of oral hygiene characterized by 3 appointments of scaling, root planning, and daily oral hygiene instructions. The patient showed marked resolution of gingival lesions and a significant improvement of related pain and gingival inflammatory indexes. Clinical Implications . This case report suggests that treatment with topical tacrolimus and professional oral hygiene may be helpful in the management of chronic oral GVHD with severe gingival involvement.